Combination immune checkpoint blockade as an effective therapy for mesothelioma. (3rd October 2018) - Fear, Vanessa S.; Tilsed, Caitlin; Chee, Jonathan; Forbes, Catherine A.; Casey, Thomas; Solin, Jessica N.; Lansley, Sally M.; Joost Lesterhuis, W.; Dick, Ian M.; Nowak, Anna K; Robinson, Bruce W.; Lake, Richard A.; et al.
ABSTRACT: Mesothelioma is an aggressive asbestos induced cancer with extremely poor prognosis and limited treatment options. Immune checkpoint blockade (ICPB) has demonstrated effective therapy in melanoma and is now being applied to other cancers, including mesothelioma. However, the efficacy of ICPB and which immune checkpoint combinations constitute the best therapeutic option for mesothelioma have yet to be fully elucidated. Here, we used our well characterised mesothelioma tumour model to investigate the efficacy of different ICBP treatments to generate effective therapy for mesothelioma. We show that tumour resident regulatory T cell co-express high levels of CTLA-4, OX40 and GITR relative to T effector subsets and that these receptors are co-expressed on a large proportion of cells. Targeting any of CTLA-4, OX40 or GITR individually generated effective responses against mesothelioma. Furthermore, the combination of αCTLA-4 and αOX40 was synergistic, with an increase in complete tumour regressions from 20% to 80%. Other combinations did not synergise to enhance treatment outcomes. Finally, an early pattern in T cell response was predictive of response, with activation status and ICP receptor expression profile of T effector cells harvested from tumour and dLN correlating with response to immunotherapy. Taken together, these data demonstrate that combination ICPB can work synergistically to induce strong, durable immunity against mesothelioma in an animal model.